Analisa Permasalahan Sticking Pada Tablet XYZ Menggunakan Metode PDCA di PT. Sunthi Sepuri - Mashabai, Ismi; Ruspendi, Ruspendi; Syauqi, Muhamad Iqbal (UNISTEK, 2022)
Analysis of the sticking problem on the xyz tablet using the PDCA method at PT. Sunthi Sepuri. Products that have a good level of quality will certainly get its own value for consumers. That's why the quality of a product is a measure of the success of a product.. Every company must carry out activities in its business and every activity has certain goals to be achieved as the direction of the implementation of its activities. To achieve this goal, it is necessary to control and supervise the day-to-day operations of the company's business. PT. Sunthi Sepuri is one of the companies in Tangerang that produces pharmaceutical products or known as pharmaceutical manufacturers and PT. Sunthi Sepuri is a subsidiary of Nugra Santana Group. During the product production process, there must be imperfections in producing tablets, resulting in defects in tablets. Problems with tablets include black spots, sticking (clots), capping (broken/split), variations in weight and variations in hardness. Based on observations for one month, the most defect problem in XYZ tablets is sticking. Fishbone Diagram is a problem solving technique that helps to think through the many possible causes of a problem to be solved. And PDCA is a model for continuous improvement by planning, doing, checking, and taking action. By finding the root cause of product defects and making continuous improvements, it is hoped that the company's products can improve